Non-Invasive Test for Assessment of Liver Fibrosis in Chronic Hepatitis B - Ye Ji Jun; Minjong Lee; Ho Soo Chun; Tae Hun Kim (The Korean Journal of Gastroenterology)
Chronic hepatitis B (CHB) is a high-risk condition that requires continuous monitoring and appropriate management during the natural course of the disease. In particular, the assessment of liver fibrosis is crucial for determining the optimal timing of antiviral therapy, evaluating the treatment response, and predicting the occurrence and prognosis of hepatocellular carcinoma (HCC) in the management of CHB. Although a liver biopsy is the gold standard for diagnosing liver inflammation, steatosis, and fibrosis, there has been a growing trend in the use of non-invasive tests, such as serum biomarkers, transient elastography, and shear wave elastography in CHB patients. This review provides a summary of the key research findings on the use of serum biomarkers and transient elastography in assessing liver fibrosis, monitoring the disease progression, and predicting the prognosis of CHB patients, with an emphasis on their clinical applicability.